Chronic stress at work and the metabolic syndrome: prospective study. Issue 7540 (20th January 2006) - Chandola, Tarani; Brunner, Eric; Marmot, Michael
Abstract: Objectives To investigate the association between stress at work and the metabolic syndrome. Design Prospective cohort study investigating the association between work stress and the metabolic syndrome. Participants 10 308 men and women, aged 35-55, employed in 20 London civil service departments at baseline (the Whitehall II study); follow-up was an average of 14 years. Main outcome measures Work stress based on the iso-strain model, measured on four occasions (1985-99). Biological measures of the metabolic syndrome, based on the National Cholesterol Education Program definition, measured in 1997-9. Results A dose-response relation was found between exposure to work stressors over 14 years and risk of the metabolic syndrome, independent of other relevant risk factors. Employees with chronic work stress (three or more exposures) were more than twice as likely to have the syndrome than those without work stress (odds ratio adjusted for age and employment grade 2.25, 95% confidence interval 1.31 to 3.85). Conclusions Stress at work is an important risk factor for the metabolic syndrome. The study provides evidence for the biological plausibility of the link between psychosocial stressors from everyday life and heart disease.